THE MEDIATING EFFECT OF DIGITAL LITERACY ON TRUST AND E-BANKING ADOPTION IN EMERGING MARKETS - Kumari, Jyoti; Singh, Praveen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the mediating effect of digital literacy on the relationship between trust and e-banking adoption in emerging markets. Despite the growing prevalence of digital technologies, e-banking adoption in emerging economies remains relatively low, largely due to concerns around trust in digital platforms and inadequate digital literacy. This study proposes a model that integrates concepts from the Technology Acceptance Model (TAM), Trust Theory, and Digital Literacy Theory to better understand how trust in e-banking platforms influences adoption behaviors, with digital literacy serving as a key mediator. A quantitative research design is employed, utilizing an online survey to collect data from a sample of 500 respondents in selected emerging markets. The study hypothesizes that trust positively influences digital literacy, which, in turn, positively impacts e-banking adoption. Furthermore, digital literacy is expected to mediate the relationship between trust and e-banking adoption. The data will be analyzed using Structural Equation Modeling (SEM) to test the proposed relationships. This research aims to provide insights into the mechanisms that drive e-banking adoption in regions with lower digital literacy, offering practical recommendations for financial institutions to improve trust and enhance the adoption of digital banking services. The findings will contribute to the academic discourse on technology adoption and digital literacy, while also informing policy and business strategies in emerging markets.